IMMEDIATE PROSTHESIS: : LITERATURE REVIEW - de Andrade Catunda da Silva, Raylena (Health and Society, 2021)
The immediate total prosthesis is a device made before the exodontia and is installed soon after the accomplishment of the same ones. Faced with a situation in which the patient encounters the remaining condemned teeth, many resist to remain edentulous while awaiting the healing phase for the manufacture of a conventional total prosthesis; thus, the total immediate prosthesis becomes an ally in these cases, promoting the return of aesthetics, phonetics, chewing and social coexistence. Through a literature review, this work aims to clarify the pertinent issues of the immediate total dentures, where they were presented their classifications, advantages and disadvantages, indications and contraindications, technique of making this prosthetic device, besides post-installation care. Searches were made in the databases Scielo, Medline, Bireme, Google academic, Capes and books; using the key words: immediate total prosthesis; immediate oral rehabilitation; oral surgery and selected articles between the years 2009 to 2019. It was possible to conclude that the advantages of the rehabilitation with immediate prosthesis are very evident, being thus an advantageous alternative of treatment.